Heteroatom-Engineered Fibrous Biocarbon Electrodes for the Superior Performance of Microsupercapacitors - Sinha P.; Pradhan L.; Balasubramaniam B.; Tyagi A.; Goswami A.; Bellan S.; Sharma A.; Sahu A.K.; Jena B.K. (My University, 2025)
A unique pyrolysis approach has been opted for the heteroengineering of green fibrous biocarbon. An in-depth electrochemical study facilitated the identification of the high-performing nitrogen-doped carbon (HDC-N) electrode as a favorable candidate for constructing a symmetric supercapacitor device. It exhibits a specific capacitance value of 150 F g-1 at 1 A g-1 and has an outstanding rate capability of 77% at 10 A g-1. The flexible/wearable microsupercapacitor (FWMSC) device constructed with an HDC-N electrode delivers an excellent energy density by showcasing 79.9 mW h cm-2 with respect to a power density of 2.98 W cm-2. The miniaturized FWMSC device shows superior cyclic stability up to 9000th cyclic voltammetry (CV) cycles with excellent mechanical flexibility under different bending angles. This study advocates for the essentiality of green pathways in designing microsupercapacitor electrodes. © 2025 American Chemical Society.